The contested status of political elites at the crossroads - Vogel, Lars; Gebauer, Ronald; Salheiser, Axel 1976- (Routledge research on social and political elites, 2019)
"Contemporary Western societies are witnessing ground-breaking social, economic and political changes at an accelerating pace. These changes are challenging the way democracy works and the role that political elites play in this system of government. Using a theoretical and empirical approach, this volume argues that political elites are urged to develop new strategies in order to achieve interest aggregation, to safeguard collective action, and to maintain elite autonomy and stability. The adaptive capacities of political elites are assessed through case studies, comparative and longitudinal analyses of their social structure, their recruitment patterns, and their attitudes. The book includes contributions from reputable scholars in the field of elite research and specialists on individual political systems across Europe and the US. It provides an analytical framework demonstrating that political elites are inevitable and potentially able to respond successfully to varying challenges. The book will be of key interest to scholars and students of political elites, democracy, comparative politics, political participation and European Politics"--